2017
DOI: 10.1177/0888406417745655
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the Content Acquisition Podcast Professional Development Process: Supporting Vocabulary Instruction for Inclusive Middle School Science Teachers

Abstract: Improving inclusive middle school science teachers’ vocabulary instruction is a critical step toward helping those professionals support the learning needs of all students. In this Institute of Education Sciences (IES)–funded project, inclusive science teachers received professional development using elements of a multimedia-based approach called the Content Acquisition Podcast Professional Development (CAP-PD) intervention process. In this article, the authors discuss the three iterative pilot studies conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 44 publications
5
37
0
Order By: Relevance
“…For example, CAP professional development process (CAP-PD) may allow for a deeper understanding British Journal of Educational Technology Vol 51 No 6 2020 of this complex topic. CAP-PD is a multimedia professional development process that utilizes an assortment of tools that include (1) "CAPs for Teachers with Embedded Modeling Videos," (2) instructional slides that can be used and adapted for immediate use, and (3) coaching and feedback on the learner's implementation of specific practices (Kennedy, Rodgers, Romig, Mathews, & Peeples, 2018). Second, the absence of a control or comparison group in this investigation was also a significant limitation to this study.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, CAP professional development process (CAP-PD) may allow for a deeper understanding British Journal of Educational Technology Vol 51 No 6 2020 of this complex topic. CAP-PD is a multimedia professional development process that utilizes an assortment of tools that include (1) "CAPs for Teachers with Embedded Modeling Videos," (2) instructional slides that can be used and adapted for immediate use, and (3) coaching and feedback on the learner's implementation of specific practices (Kennedy, Rodgers, Romig, Mathews, & Peeples, 2018). Second, the absence of a control or comparison group in this investigation was also a significant limitation to this study.…”
Section: Limitationsmentioning
confidence: 99%
“…Thirty-eight TESE studies examined the effectiveness of different pedagogical approaches to improving teacher learning (e.g., coaching, video analysis, and multicomponent innovations that include some combination of knowledge development, modeling, practice, and feedback; see Online Appendix A). The vast majority were designed to improve teachers’ knowledge and skill for implementing evidence-based practice (e.g., Kennedy, Rodgers, Romig, Mathews, & Peeples, 2018; Sayeski, Hamilton-Jones, Cutler, Earle, & Husney, 2019). A summary of the research supporting each pedagogical approach follows.…”
Section: Teacher Education Research Since 2010mentioning
confidence: 99%
“…The second largest set of studies used mostly single-subject, experimental and quasi-experimental methodologies to demonstrate the efficacy of multicomponent approaches for increasing teachers’ knowledge, instructional skills, and/or student outcomes in a variety of areas (e.g., functional behavioral assessment, vocabulary instruction, and elementary reading, writing, and mathematics instruction) using mostly single-subject and quasi-experimental designs (see Online Appendix A). Multicomponent innovations incorporated some combination of initial training in strategies (and sometimes content knowledge underlying those strategies) with at least two or more of the following active learning opportunities: modeling, practice in structured settings, action research projects, professional learning community, and/or feedback (e.g., Browder et al, 2012; Cavazos, Linan-Thompson, & Ortiz, 2018; Hoover & Soltero-González, 2018; Horrocks & Morgan, 2011; Kennedy et al, 2018; Lembke et al, 2018). Findings from 10 studies showed that multicomponent interventions were able to change teachers’ use of discrete instructional behaviors (e.g., Horrocks & Morgan, 2011) and more complex instructional routines (e.g., Kennedy et al, 2018; Lembke et al, 2018).…”
Section: Teacher Education Research Since 2010mentioning
confidence: 99%
See 2 more Smart Citations